A study on phobia among selected UPVTC students second semester, AY 2008-2009 - Boco, Glena (2009)
The study aimed to determine if there are students in UP Tacloban who have phobias, to identify the specific of phobia of each student, to identify the causes of their phobias, and to determine the coping mechanisms used by the students towards their phobias. A total of 100 participants were randomly selected. The questionnaire was used to gather the needed data. 25% of the participants were identified phobic and 75% were nonphobic. Out of the 25 phobic students, 10 were interviewed to determine their phobias, how and when did it begin, the physiological manifestations, and the coping mechanisms imply do to avoid their phobic object. The most common types of phobia that the students have that there are situational phobia, animal phobia and social phobia. A specific stressful event usually triggers the development of a specific phobia. Responses to fear varied from screaming to immobilization. All of them felt their fear excessive and unreasonable. The majority of the interviewees felt that their fear does not interfere with their normal routine. Some was quite unsure and thinks that it depends on the level of the exposure to their feared object or phenomena. Majority of them does not want to be treated because of the knowledge that treatment will include exposure to the phobic objects. Recommendations on further conducting studies on phobia are given.
Undergraduate thesis (B.A.S.S. Psychology) -- University of the Pjilippines, Tacloban.
Keywords: Psychology